Nurses' knowledge and attitudes in promoting exclusive breastfeeding - Chiu, Ai Moi. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Breast milk is the most essential nutrition for newborn in meeting their rapid physical growth and mental development. Other than that it advantage the mothers in preventing postpartum hemorrhage, act as natural contraception and reduce risk for breast cancer. For these reason, breastfeeding is highly recommended to all mothers. However, the survey done in 1996 shown that in Malaysia, only 29% mother breastfeed their child while 86.1 % choose to bottle feed. Few researches have been carried out to determine the causes of the low prevalence. Most of it was assessing the factors influencing mothers not to breastfeed. Even though mothers is the one who decide whether to breastfeed or not, their decision still be influenced by health care professional. Thus, this study was done to assess the nurses' knowledge and attitudes in promoting exclusive breastfeeding. This quantitative, descriptive-exploratory study was done in three major Maternal and Child Health Clinic namely MCH Jawa, MCH Sekama and MCH Tanah Puteh. A sample of 42 registered nurses was recruited from these three MCH based on purposive sampling. Data were collected using a self-administered questionnaire. The overall finding indicated nurses have high knowledge and held positive attitudes in promoting exclusive breastfeeding especially nurses graduated from Sarawak Junior Chamber Program and were married. In the section assessing nurses' attitudes, most nurses score high point in these three aspects: perception of exclusive breastfeeding, nurses' role in promoting exclusive breastfeeding and nurses' involvement in problem solving. Based on the findings, the results have significant implicate to further improve their knowledge and attitude through education, practice and research.